Enhancing Analyst by integrating the R package ‘Luminescence’ - Duller, G. A. T. (Ancient TL, 2018)
A new facility within the software package Analyst is described, allowing users to run R scripts with little or no need to interact directly with the R language themselves. This tight integration of R within Analyst provides users with a much more powerful platform in which to undertake selection and analysis of their data than is currently available. The current implementation focusses on the use of the R ‘Luminescence’ package for visualisation and statistical modelling of equivalent dose distributions, but the wide variety of other capabilities of the R statistical language can also be accessed using this new system. For users with more experience of using R, this new version of Analyst allows them to tailor their analysis in a way that is specific to their application, whilst retaining the simplicity of the Analyst interface. The ability to exploit the complex statistical methods available in R from within the Analyst environment provides a powerful new approach to data analysis in luminescence research.